Synthesis And Biological Evaluation Of 2-Substituted Benzimidazoles - B.N.B.VAIDEHI; K.GNANA DEEPIKA (International Journal of Pharma and Bio Sciences, 2012)
A set of 2-substituted benzimidazoles were successfully synthesized. Benzimidazoles were prepared by condensation of ortho-phenylenediamine with substituted acids in presence of ring closing agents like Polyphosphoric acid/ HCl. The synthesized compounds were characterized by IR spectroscopy and Elemental analysis. All the synthesized compounds were screened for anthelmenthic activity by using Albendazole as standard.